Metaphorical Exemplification of Emotions in Pure Music - Mikalonytė, Elzė Sigutė (Problemos, 2019)
[full article and abstract in Lithuanian; abstract in English]In this paper, it is argued that pure music does not represent emotions but it can metaphorically exemplify them. This proposition is based on Nelson Goodman’s conception of metaphorical exemplification which is supplemented by Mark Textor with an additional condition of intention (exemplification requires an intention to exemplify). The paper consists of two parts. In the first part, an analysis of recognition and evocation of emotions when listening to music is presented. In the second part, a new argument is offered for considering the metaphorical exemplification of emotions in music as a non-natural type of meaning in a Gricean sense. By accepting this premise, the conception of metaphorical exemplification can be defended against main criticisms.
Keywords: emotional expressivity of music; metaphorical exemplification; Nelson Goodman; Paul Grice